2014
DOI: 10.1136/sextrans-2013-051397
|View full text |Cite
|
Sign up to set email alerts
|

A peer-led, community-based rapid HIV testing intervention among untested men who have sex with men in China: an operational model for expansion of HIV testing and linkage to care

Abstract: Trained peers providing rapid HIV testing with social support and case management through the early period following diagnosis can efficiently expand HIV testing and improve linkage to care among MSM in China.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
61
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(66 citation statements)
references
References 18 publications
2
61
0
Order By: Relevance
“…This is because communicating with a peer could lessen the anxieties of HIV-positive MSM who have not yet initiated care; peer-initiated care might be carried out in MSMfriendly manner with flexible schedules in convenient locations. 11 Thus, this approach would address several barriers such as time or location inconvenience, stigma, and discrimination associated with traditional hospitals and clinics. In addition, the vast development of electronic technology (emails, short message service text messaging via cell phone, QQ, WeChat, Grinder, and others) been popular among Chinese MSM.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This is because communicating with a peer could lessen the anxieties of HIV-positive MSM who have not yet initiated care; peer-initiated care might be carried out in MSMfriendly manner with flexible schedules in convenient locations. 11 Thus, this approach would address several barriers such as time or location inconvenience, stigma, and discrimination associated with traditional hospitals and clinics. In addition, the vast development of electronic technology (emails, short message service text messaging via cell phone, QQ, WeChat, Grinder, and others) been popular among Chinese MSM.…”
Section: Discussionmentioning
confidence: 99%
“…Six FGD were conducted, including four among HIVpositive (11,10,10, and 9 participants in each group) and two among HIV-negative or status-unknown MSM (10 in each group, but with 4 status-unknown participants in negative group #2). For this study's purposes (identify the barriers to and facilitators of linkage to HIV care), we analyzed qualitative data from the four focus groups with HIV-positive MSM only.…”
Section: Data Collectionmentioning
confidence: 99%
See 1 more Smart Citation
“…A Nigerian study found that peer outreach workers/case managers are able to identify MSM living with HIV and engage them in care[89]. A Chinese study found that peer-led HIV testing with case management among MSM led to a higher proportion of MSM screened receiving their test result and a higher proportion of those positive being linked to care[90]. Peer networks have been used to identify PWID living with HIV who are out of care in Russia[91].…”
Section: Recent Work In Interventions To Improve Outcomes For Key Popmentioning
confidence: 99%
“…Last but by no means least, we report STI outcomes of a randomised trial of microbicides,12 a review of HIV prevalence in military populations,13 the use of condoms for contraception in HIV infected clients,14 HIV outcomes in drug using sex workers,15 and a model of the dual impact of HIV therapy and sexual behaviour changes in Uganda,16 chlamydial seroprevalence in the Netherlands17 and peer led HIV testing in China 18. I hope you will find this month’s issue as fascinating as I did!…”
mentioning
confidence: 99%